(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The publication deals with methodological aspects of the shadow economy evaluation. The aim of the article is to carry out a critical analysis of monetary evaluation methods of the shadow sector and to investigate the possibility of their application to the national economy of Ukraine. Basic methodical ways and techniques of monetary approach are examined. The advantages and disadvantages of the monetary methods of evaluation of the shadow economy volume are analysed. The limited possibilities of using monetary methods under conditions of unstable economic development are grounded. The attention is paid to the fact that the choice of appropriate methods of the shadow economy evaluation is caused by the national characteristics of the country, the purpose of the study and depends on the situation. Official data of evaluation of the shadow sector in Ukraine are presented.